Establishment of an end-to-end 3D dosimetry system for radiotherapy of the brain using complementary metal oxide semiconductor-optical computed tomography (CMOS-OCT) and PRESAGE radiochromic polymer dosimeter / Muhammad Zamir Mohyedin - Mohyedin, Muhammad Zamir (2023)
Advanced radiotherapy techniques require a three-dimensional (3D) dosimetry system that is capable of measuring the complex dose delivery accurately. Available dosimeters are mostly in one-dimensional (1D) and two-dimensional (2D), which have limitations to evaluate the volumetric dose distribution from the advanced radiotherapy techniques. This study attempts to establish an end-to-end 3D dosimetry system for radiotherapy of the brain using a PRESAGE dosimeter and an anthropomorphic phantom that is readout using a complementary metal oxide semiconductor-optical computed tomography (CMOS-OCT) system. The characterisation of the CMOS-OCT/PRESAGE system was performed by investigating the dose uniformity, linearity, dose-rate dependency and percentage depth dose (PDD). The dosimetric properties of PRESAGE measured by the CMOS-OCT system were investigated and compared with the external beam therapy (EBT) film. Ultraviolet-Visible (UV-Vis) spectroscopy was used to verify the optical density (OD) change measured by the CMOS-OCT system. It was found that the OD of PRESAGE measured by the CMOS-OCT system demonstrated a linear dose response with the R2 better than 0.984. The system shows dose rate independency from 100 to 800 cGy/min with a less than 3% variation. The system illustrated an excellent agreement of the PDD profile with the ionisation chamber. These characterisation results demonstrated that the CMOS-OCT/PRESAGE system has potential for radiotherapy dosimetry. The CMOS-OCT/PRESAGE system also illustrates good agreement with standard dosimeter (EBT films) and with standard measurement system (UV-Vis spectroscopy).The performance of the PRESAGE dosimeter was evaluated by investigating the dose response under room temperature (27° C), control temperature (3°C to 5°C), exposure to visible light, fading response, reusability and reproducibility for the complex radiotherapy dose delivery. The irradiation was performed using a linear accelerator at 6 MV and 10 MV photon beam energy.